Taxonomia de Mnioes Townes, 1946 (Hymenoptera: Ichneumonidae: Banchinae) do Uruguai - Teixeira, Gabriel Medrado (Entomologia, 2023)
Mnioes Townes, 1946 (Hymenoptera: Ichneumonidae: Banchinae) belongs to a group of Darwin’s Wasps, found mainly in the Neotropics. A taxonomic study of specimens of Banchinae from the Uruguayan fauna deposited in the National Institute of Amazonian Research (INPA) collection was carried out, Where 90 specimens of Mnioes were examined. Specimens were identified and Illustrated, with a total of six species identified, incluiding four new species. The species Mnioes pusaq Alavarado, 2020 and Mnioes attenboroughi Alvarado, 2020 had their records expanded and were recorded for the first time in Uruguay. In addition, two morphotypes (based on males only) were illustrated (Mnioes sp. A and Mnioes sp. B). Also, morphological characters and digital images were added, an illustrated dichotomus identification key, also providing maps with geographic records for all species presente in Uruguay.
Keywords: Taxonomia; Ichneumonidae; Banchinae